Virasoro amplitude from the S(N) R**24 orbifold sigma model - FROLOV, SERGEY (Springer, 1998)
Four tachyon scattering amplitude is derived from the SNR24 orbifold sigma model in the large N limit. The closed string interaction is described by a vertex which is a bosonic analog of the supersymmetric one, recently proposed by Dijkgraaf, Verlinde and Verlinde.
PUBLISHED
Keywords: Mathematics; orbifold model